2005
DOI: 10.1637/7366-041205r.1
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Combined Effects of Fusarium moniliforme Culture Material, Containing Known Levels of Fumonisin B1, and Salmonella Gallinarum Infection on Liver of Japanese Quail

Abstract: Three hundred day-old Japanese quail (Coturnix coturnix japonica) were divided into two groups with 150 quail in each group. One group was maintained on quail mash alone, while Fusarium moniliforme culture material was added to quail mash in the second group from day 5 of age and was supplied at a rate of 150 ppm fumonisin B1 (FB1)/kg mash. At day 21, each group was further subdivided into two groups, yielding four groups with 75 birds apiece, which served as the control (group CX), the Salmonella Gallinarum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The changes in the liver and kidneys of broiler chicks fed OA in the present study are similar to those reported by Huff et al (1974Huff et al ( , 1975, Prior et al (1976), Dwivedi & Burns (1984a), Mohiuddin et al (1992) and Sandhu et al (1995). Gross and histopathological changes in the liver and kidneys recorded following S. Gallinarum infection were also similar to those reported by Chishti et al (1985), Kaushik et al (1986), Sandhu et al (1987), Kokosharov et al (1997), and Deshmukh et al (2005) in the liver and/or kidney of birds affected naturally or experimentally with S. Gallinarum. The changes in both organs were more severe in the combination group (fed OA and inoculated with S. Gallinarum) than in either of the individual groups.…”
Section: Discussionsupporting
confidence: 91%
“…The changes in the liver and kidneys of broiler chicks fed OA in the present study are similar to those reported by Huff et al (1974Huff et al ( , 1975, Prior et al (1976), Dwivedi & Burns (1984a), Mohiuddin et al (1992) and Sandhu et al (1995). Gross and histopathological changes in the liver and kidneys recorded following S. Gallinarum infection were also similar to those reported by Chishti et al (1985), Kaushik et al (1986), Sandhu et al (1987), Kokosharov et al (1997), and Deshmukh et al (2005) in the liver and/or kidney of birds affected naturally or experimentally with S. Gallinarum. The changes in both organs were more severe in the combination group (fed OA and inoculated with S. Gallinarum) than in either of the individual groups.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies with one high concentration of fumonisins in the feed have been published since then, demonstrating that fumonisins potentially may have toxic effects in quails. Increased mortality, ruffled feathers, reduced feed intake and body weight gain and increased pathological alterations after infection with Salmonella Gallinarum and effects on spleen and lymphoid cell depletion in tissues have been reported from feeding studies where quails were a given single dietary feed concentration from 150 mg FB 1 /kg feed (see Table , Asrani et al., ; Deshmukh et al., ,b, ; Sharma et al., ). Reduced feed consumption and bw gain and reduced egg weight were also reported from laying quails given a feed containing 10 mg FB 1 /kg feed from F. verticillioides culture material for 140 days (5 egg laying circles of 28 days) (Ogido et al., ), but even in this study only one feed concentration was used and no reference points could be identified.…”
Section: Assessmentmentioning
confidence: 98%